Effect of Eucommia ulmoides Leaf Extract on Chronic Dextran Sodium Sulfate-Induced Colitis in Mice - Takatori, Shingo; Murakami, Satoshi; Tasaka, Yuichi; Kawasaki, Hiromu; Araki, Hiroaki; Tanaka, Akihiro (Biological & pharmaceutical bulletin, 2018)
Ulcerative colitis (UC) is a refractory disease that causes chronic inflammation or ulceration in the mucosa of the large intestine with multiple relapses. Although several drugs, including 5-aminosalicylic acid, steroids, immunosuppressants, and infliximab, are used for UC therapy, patients suffer from side effects of these drugs, and a new safer therapeutic agent is desired. Eucommia ulmoides OLIV. leaf extract (ELE) has an anti-inflammatory effect. Therefore, we examined the effect of ELE on UC using a chronic dextran sulfate sodium (DSS)-induced colitis model in mice. Chronic DSS-induced colitis was triggered by alternately repeating 5 days’ DSS and 7 days’ water administration in mice for 29 d. The severity of DSS-induced colitis was evaluated by daily body weight and bloody stool score, and colon length and myeloperoxidase (MPO) activity in colon tissue on day 29. ELE (3 or 9%) was administered in combination by feeding for 29 d, and the effect on colitis was evaluated. The mice given DSS exhibited chronic colitis symptoms with body weight loss, increased bloody stool score and MPO activity, and shortened colon length. Administration of 3 or 9% ELE suppressed the body weight loss, bloody stool score, colon shortening, and MPO activity in a dose-dependent manner. Histological analysis showed that the ELE-treated mice had less damages and leukocyte infiltration in the mucosal layer of the large intestine compared to DSS alone group. These results suggested that ELE has the potential to prevent the development of DSS-induced colitis and a therapeutic effect on UC in a safe manner.